FASE PERKEMBANGAN ANAK DAN POLA PEMBINAANNYA DALAM PERSPEKTIF ISLAM - Khusni, Moh. Faishol (IAIN Tulungagung, 2018)
This research aims to study further about Islamic concept regarding with children, their development stages and up-bringing pattern in Islamic perspective as one of its scientific contribution for the success of educating children. This research also compares the perspective of psychology and Islam and the practical framework of developing children up-bringing in accordance with Islamic teaching. This is a library research with heurmeneutis-psychology approach by revealing texts from Al-Qur’an and Al-Hadith as well as other relevant sources which have psychology contents. The data was analyzed using comparative method and content analysis. From this research, it can be concluded that Al-Qur’an and Al-Hadith divide children development in two stages; they are early ath-thifl stage (0-7 years old) and late ath-thifl stage (7-14 years old). Therefore, based on this understanding of development stage the teaching pattern can be adapted starting from the early ath-thifl stage by implementing a’dib approach that is identifying self with the children, and implementing addib approach during late ath-thifl stage, that is by teaching discipline. From this research, it can be concluded that Islamic teaching also has clear guideline to bring up children from the day they are born until adolescence in accordance with their development stages.